Experimental Investigation of the Flexural Bearing Capacity of Pull-Up Cantilever Scaffolds with Adjustable Steel Tie Rods - Zhanbo Huang; Jianjun Yang; Shizhong Zhou; Chenyang Zhang; Jintao Yang (Buildings)
This study presents experimental investigations of the flexural bearing capacity of the lower load-bearing structures of pull-up cantilever scaffolds with adjustable steel tie rods. First, load-bearing structures with three different specifications are tested to analyze their primary failure modes and failure mechanisms. The experimental results are then simulated and validated using a finite element analysis (FEA) method. Subsequently, an extended parametric analysis is performed numerically, and a simplified calculation formula is derived through nonlinear curve fitting to evaluate the load-bearing capacity. Finally, the effects of the transverse spacing of the vertical rods, the length of the cantilever beams, and the spacing of the hanging ears on the flexural bearing capacity of the structures are analyzed.